Pedagogic principles of the clergymen at San Viator and their implementation in the school scene in Asturias (1912-1941) - Martínez Cardín, Andrés (Historia y Memoria de la Educación, 2020)
The presence in Spain of the French congregations devoted to education comes determined by the political events that took place during the III Republic in the neighbouring country starting at the end of 19th century. Like many others, , clergymen from San Viator, a congregation founded by the French priest Luis Querbes and devoted to education since 1851, arrived in Spain in 1903 with the aim of finding refuge and continuing their educational work. After settling at a first stage in the city of Vitoria (Basque Country, Spain), they soon developed a program of foundations in the nearby surroundings which culminated with their establishment of a centre in Asturias (north-central Spain). With the approval of the diocese and the parish, they opened their first school in 1912, in the Asturian village of Cangas de Onís, which was soon followed by other twin foundations in Ribadesella and Infiesto. Our article undertakes to review their presence in the area - largely ignored today in the school scene of our region - by analysing those pedagogic principles which inspired their dedication to the school, their educational offer and their capacity for innovating and adapting to the interests of an industrial society aspiring to secure a top-class education for their pupils. For this commitment they used, among other things the regional press as an advertising resource that was able to guarantee them the prestige attained in the region along their educational journey.